Shaping the future of wireless communication: An analysis of reflectarray antennas for 5G/6G - Abbasi, Muhammad Inam; Sohu, Izhar Ahmed; Mohd Ibrahim, Imran; Sohoo, Arslan Ahmed; Sulaiman, Noor Hafizah (Penerbit UTM Press, 2025)
The rapid development of intelligent emerging applications and technologies requires a huge data rate along with reliable and efficient connectivity. Each new generation is better than the last one in several ways. Fifth Generation (5G) communication represented various features as compared to 4th generation communication. However, 5G specifications severely limit on demands of innovative emerging technologies. Which include a high data rate, more capacity, low latency, reliability, resource sharing, and energy per bit. While testing phase for 5G is ongoing in most countries, the 6G technology has become the focus of modern research. In this paper, we discuss the implementation of 6G projects worldwide, requirements, and 6G emerging technologies applications such as Multi-Sensory XR, Robotics and Autonomation, Smart and Remote Healthcare, Internet of Everything (IoE), Wireless power transfer and Wireless Brain Computer Intercommunication. Reflectarray antenna (RAs) are a potential antenna for 5G and 6G systems because they have many advantages including high gain, beam modelling, beam scanning, reconfigurability, and multiple beams. This study represents a comprehensive review of the design of single and dual band reflectarray antenna in some specific research areas. The development of several design operations for improving the reflection phase, gain, and efficiency are covered in detail. Several methods of enhancing the unit cell reflectarray featured properties to make them 5G-compatible.